Improvement in advanced pancreatic cancer survival with novel chemotherapeutic strategies – experience of a community based hospital - Hann, A.; Bohle, W.; Egger, J.; Zoller, W. G. (Zeitschrift für Gastroenterologie, 2016)
Background: New chemotherapeutic strategies for locally advanced or metastatic pancreatic ductal adenocarcinoma (PDAC) have been shown to improve survival in randomized clinical trials. Little is known about the use of such chemotherapies and their benefit in community-based hospitals. This retrospective study analyzes the overall survival of these patients under “real life conditions” before and after the introduction of FOLFIRINOX in 2011.Methods: We retrospectively identified consecutive patients with PDAC who were treated at our hospital from 2011 to June 2014 (2011+ cohort) and 2004 to 2010 (historical cohort). Patients were included if PDAC was diagnosed in a locally advanced or metastatic state and at least 1 cycle of chemotherapy was given. Survival was assessed until April 2016. Patients with FOLFIRINOX were further analyzed regarding drug administration and side effects.Results: 128 patients met the inclusion criteria. Of the 74 patients in the historical cohort, 62 patients received Gemcitabine. Of the 54 patients diagnosed between 2011 and June 2014, 28 patients received FOLFIRINOX and 22 Gemcitabine as the first-line chemotherapy. Only 34 % of the patients in the historical cohort received a second-line chemotherapy in comparison to 69 % in the 2011+ cohort. Median overall survival (OS) showed a survival of 13.1 months (95 % CI; 11.6 – 14.5) for the 2011+ cohort compared to 9.6 months (95 % CI; 6.1 – 13.1) in the historical group.Conclusion: This study shows a marked improvement in survival of patients diagnosed with locally advanced or metastatic PDAC in a community-based hospital during the past 4 years. The most likely reasons are the use of new polychemotherapies like FOLFIRINOX and the use of second-line chemotherapy.
Keywords: Pankreaskarzinom; Gesamtüberleben; FOLFIRINOX; Kommunales Krankenhaus; Chemotherapie